Investigating the applicability of immune checkpoint blockade in upper gastrointestinal cancers - Davern, Maria (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2022)
Oesophagogastric junctional adenocarcinoma (OGJ) is an aggressive malignancy with a high propensity to metastasise. Response rates to first-line chemo(radio)therapy regimens remain poor therefore, better treatment options are required to improve clinical outcomes for OGJ patients. Combining ICB with immunostimulatory chemotherapies to boost response rates is an attractive approach for converting cold non-inflamed tumours into hot inflamed tumours, which typically respond better to ICB. This body of work highlighted the cooperation between ICB and first-line chemotherapy regimens to boost anti-tumour immunity and decrease the survival of OGJ cells via immune-independent and immune dependent mechanisms. FLOT (5-FU, oxaliplatin, docetaxel) and CROSS chemotherapies (CT) (paclitaxel, carboplatin) regimens induced immunogneic cell death in OGJ cells and icnreaed the cytotoxic potential of healthy donor T cells. Post-FLOT and post-CROSS CT tumour cell secretome enhanced lymphocyte-mediated killing of OGJ cells highlighting the immunostimulatory potentail of first-line chemtoherapy regimens. Pro-inflammatory T cell cytokine profiles were enhanced by first-line chemotherapy regimens. This body of work demonstrated that FLOT and CROSS CT regimens decreased co-stimulatory marker CD27 expression and increased co-stimulatory markers CD69 and ICOS expression on the surface of T cells. However, ICB attenuated chemotherapy-induced downregulation of CD27 on T cells and promoted differentiation of effector memory T cells into a terminally differentiated state. Importantly, dual nivolumab-ipilimumab treatment enhanced OGJ lymphocyte-mediated cytolysis of OE33 cells. This study also profiled immune checkpoint (IC) expression to help guide design of rational ICB and chemotherapy combinations in the first-line setting. Expression of ICs on T cells positively correlated with a subsequent poor response to neoadjuvant treatment and more advanced tumours. First-line chemotherapy regimens substantially altered IC expression profiles of T cells increasing PD-1, A2aR, KLRG-1, PD-L1, PD-L2 and CD160 and decreasing TIM-3 and LAG-3 on OGJ donor T cells. These findings highlight a link between chemotherapy and the development of immune-resistance, reaffirming the rationale to administer ICBs concurrently with first-line chemotherapies to prevent potential IC-mediated suppression of chemotherapy-induced anti-tumour immunity. Interestingly, this study also identified that PD-1, PD-L1, A2aR and TIGIT ICs expressed on the surface of OGJ cells possessed novel immune-independent functions and could promote a range of hallmarks of cancer including proliferation, DNA repair, metabolism, pre-survival signalling and chemoresistance. Blockade of PD-1, PD-L1 or A2aR enhanced the toxicity of FLOT chemotherapy in OGJ cells. In addition, this body of work identified that blockade of PD-1 signalling in OGJ cells decreased tumour cell survival however, under glucose deprived or hypoxic conditions PD-1 blockade provided OGJ cells with a survival advantage. Given that PD-1 blockade enhanced basal respiration and glycolytic reserve it may be the case that under these conditions PD-1 blockade promoted a metabolic phenotype that was more adaptable. Collectively, this highlighted an immune-independent explanation for resistance to PD-1 ICBs in hypoxic tumours other than suppression of immune responses. In contrast, TIGIT blockade decreased survival of OGJ cells under full nutrient and normoxic conditions as well as hypoxic and nutrient deprived conditions suggesting that TIGIT blockade may be a more suitable ICB to target OGJ cells in hypoxic tumours. Hostile features of the tumour microenvironment including glucose deprivation, serum deprivation, hypoxia and acidosis all had profound effects on the IC expression profile of OGJ patient-derived T cells. A range of ICs were significantly upregulated on the surface of T cells which may contribute to T cell dysfunction. LAG-3, TIGIT and A2aR have been implicated in promoting a regulatory T cell phenotype and pre-clinical studies have demonstrated that blockade of these ICs promoted tumour regression in murine studies. This body of work demonstrates that hostile features of the tumour microenvironment create exploitable targets that could be harnessed with the use of novel ICBs targeting A2aR, TIGIT and LAG-3 in combination with conventional ICBs that target the PD-1 and CTLA-4 axes. ICB increased IFN-γ production by T cells under moderately acidic conditions this effect was abrogated under severe acidic conditions highlighting the ability of acidosis to potentially limit ICB efficacy. A rationale for administering oral neutralizing buffers in conjunction with ICB in OGJ patients to limit the immunosuppressive effects of tumour acidosis on the efficacy of ICB is highlighted. Visceral adipose tissue plays a significant role in tumour initiation, development and progression via generation of chronic systemic low-grade inflammation via release of pro-inflammatory factors into circulation. Therefore, this study investigated the effect of the visceral adipose secretome on T cell activation status and IC expression profiles. These findings demonstrated that adipose conditioned media (ACM) from both early and late stage OGJ patients enhanced T cell activation status and upregulated CTLA-4 on the surface of Th1-like cells and Treg cells and increased PD-L1 on the surface of Treg cells. Thus, creating a therapeutic niche for harnessing anti-cancer immunity with the use of ICB targeting CTLA-4 and PD-L1. Importantly, the addition of ICB in the presence of ACM decreased the production of pro-inflammatory tumour-promoting cytokines IL-17 and TNF-α which have been reported to drive malignant progression.
APPROVED
Keywords: chemotherapy; immune checkpoint blockade; TIGIT; PD-1